Challenges and strategies for Chinese fintech firms compliance operations in Indonesia: Case studies and regional comparative analysis - Tengfei, Wang; Alam, Hazlina Binti Shaik MD Noor (Edelweiss Applied Science and Technology, 2025)
This study dissects the compliance pain points facing Chinese fintech firms in Indonesia and offers actionable guidance for overseas expansion. Design/Methodology: Using a three-step framework—regulatory mapping, regional comparison (China–Singapore–Malaysia), and corporate case analysis (Akulaku, DANA, AdaKami, Kredivo; RupiahPlus)—the paper evaluates barriers and countermeasures. Findings: Indonesia’s regime has tightened and diversified: the 2022 Personal Data Protection Law (PDP Law) introduces extraterritoriality, data minimization, 72-hour breach notice, and “equivalent protection” for cross-border transfers, raising data-compliance costs; the 2023 P2SK Law moves crypto oversight from Bappebti to OJK from 2025; POJK No. 40/2024 eases foreign equity caps while increasing capital/disclosure requirements and banning aggressive collections. A dual-track BI–OJK structure, Kominfo oversight, and local autonomy create fragmented standards and heavier reporting/enforcement burdens. Conclusion: China’s internet-finance model is not directly transferrable to Indonesia. Practical implications: Firms should build a dual adaptation framework—institutionally, dynamic regulatory mapping and localized data-governance plans; culturally, product and process designs compatible with religious-legal norms—plus staged market-entry and compliance operating models.